Comparison of residual geometric errors obtained for lung SBRT under static beams and VMAT techniques: Implications for PTV margins. (August 2018) - Vloet, Anita; Li, Winnie; Giuliani, Meredith; Seco, Petula; Silver, Lauren; Sun, Alexander; Bissonnette, Jean-Pierre
Highlights: VMAT reduces time spent on bed for Lung SBRT patients compared to static beams. The average residual positional errors are less for patients treated with VMAT. Introducing VMAT for lung SBRT could reduce setup margins from 5 mm to 3 mm. However, we recommend maintaining a 5 mm margin to further reduce time on bed.